2020
DOI: 10.1186/s12917-020-02699-4
|View full text |Cite
|
Sign up to set email alerts
|

Demography and determinants of dog and cat ownership in three towns of West Shoa zone, Oromia Region, Ethiopia

Abstract: Background The dog and cat population data is generally scarce in developing countries due to absence of surveys. The demography of owned dogs and cats, and the associated ownership characteristics, are essential for the control of pet population and zoonosis. This study was conducted in three towns of West Shoa Zone of Ethiopia with the objectives of assessing demographic characteristics of owned dogs and cats and determinants of ownership. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…These might suggest the ubiquitous nature of the parasites and that these factors have a similar risk of infection as reported by other researchers elsewhere [35,38,39,43]. Besides, the lack of association of T. gondii seropositivity with breed and sex of dogs might have probably be overshadowed by the high exposure to the parasite at a very young age [30,33]. In agreement with the present study, Kalayou et al [14] also reported the absence of a significant association between sex, housing, and place of residence and L. donovani seroprevalence in dogs of northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…These might suggest the ubiquitous nature of the parasites and that these factors have a similar risk of infection as reported by other researchers elsewhere [35,38,39,43]. Besides, the lack of association of T. gondii seropositivity with breed and sex of dogs might have probably be overshadowed by the high exposure to the parasite at a very young age [30,33]. In agreement with the present study, Kalayou et al [14] also reported the absence of a significant association between sex, housing, and place of residence and L. donovani seroprevalence in dogs of northwest Ethiopia.…”
Section: Discussionsupporting
confidence: 65%
“…This might indicate that climate considerably influences the risk of T. gondii exposure. The warm and moist environment coupled with the more abundance of cats [30] and the source of infection for dogs (cats, the meat of infected domestic or wild animals containing tissue cysts) in Bako town might explain the higher seroprevalence. It has been well documented that seroprevalence varies according to the density of cats and intermediate hosts [19], geographical location, and even within the same region from place to place.…”
Section: Discussionmentioning
confidence: 99%
“…Male dogs were slightly more abundant than the female dogs and the sex ratio was estimated at 1.2 (rural site) and 1.3 (urban site) as for other reports ( Tschopp et al., 2016 ; Kardjadj et al., 2019 ; Tasiame et al., 2019 ). Such imbalance can be explained by the fact that female dogs are euthanized by their owners to avoid disturbance during the breeding season ( Pal, 2001 ; Gebremedhin et al., 2020 ). In addition, others reported that dog owners prefer males to females because they attribute to them better capabilities on their duties of guarding and farming ( Kitala et al., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Donkeys, mules, and horses provide pack and transportation services in both urban and rural settings [ 5 , 6 ]. Dogs and cats are companion animals; in addition, dogs provide guard services [ 7 ]. Nevertheless, many factors hamper their optimal socioeconomic contribution, as parasitism in general, and ixodid ticks and associated pathogens in particular, poses substantial health threats to these animals.…”
Section: Introductionmentioning
confidence: 99%